Differenzialdiagnostik der physiologischen Herzhypertrophie (Sportherz) - Dickhuth, H. H.; Hipp, A.; Niess, A.; Röcker, K.; Mayer, F.; Horstmann, T. (Deutsche Zeitschrift für Sportmedizin, 2001)
The need to differentiate between physiological and pathological hypertrophy is frequently encountered in a (sports) cardiological outpatient clinic and has both prognostic and therapeutic impact. The characteristics of physiological hypertrophy are described, then the essential differential diagnostic criteria for hypertension-related hypertrophy, non-obstructive cardiomyopathy and dilatative cardiomyopathy are discussed. While pronounced pathological forms of hypertrophy present hardly any diagnostic difficulties, even in athletes, early or only slightly developed forms are often difficult or impossible to recognize, even with invasive methods, and can best be assessed by their course.